Mental health and violent youth: a developmental, lifecourse perspective - Boots, Denise Paquette (Criminal justice recent scholarship, 2008)
Violence and chronic offending as a social phenomenon -- Exploring the relationship between childhood XE "childhood" mental health problems and violent behaviors -- Developmental modeling of DSM-oriented problems and serious offending behaviors in youth -- Findings regarding youth violence and property crime -- Implications and conclusions